Technological characterization and molecular identification of defined protective starter cultures for fermentation of traditional Rayeb made from camel's milk. Issue 2 (28th July 2022) - Abozead, Rania; Kheadr, Ehab; Safwat, Nabil; Salam, Samir; Dabour, Nassra
Abstract: Camel milk isolates of lactic acid bacteria were characterized to develop defined starter cultures that could be used for the production of standardized Egyptian Rayeb fermented milk. The isolates have shown a wide diversity of Technological characteristics and antimicrobial activity. Interesting isolates were genetically identified at the species level. Two mixed culture starters composed of Lactiplantibacillus plantarum (FFNL146 and FFNL159) and Lactococcus lactis (FFNL1926 and FFNL2005) along with Leuconostoc pseudomesenteroides FFNL2374 were used in the production of Rayeb from camel milk, cow milk, and their mixture and stored for 14 days under refrigeration. Equally mixed camel and cow milk fermented with both starters had the best results of organoleptic attributes and physicochemical properties compared to samples made of camel milk. This is the first study to present two mixed starter cultures for Rayeb manufacturing. The success of these defined starter cultures will potentially enhance the safety and quality of the Rayeb industry in Egypt. Abstract : Molecular identification and characterization of defined starter cultures for fermentation of Rayeb.